Vitamin and Trace Minerals: A Survey of Current Feeding Regimens - J. R. Flohr; M. D. Tokach; J. C. Woodworth; J. M. DeRouchey; S. S. Dritz; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2015)
Swine producers and nutritionists representing production systems across the United States were surveyed about added vitamin and trace mineral concentrations in swine diets used from March to August of 2014. Respondents were asked to provide the vitamin and trace mineral premix specifications and inclusion rates to calculate complete diet added vitamin and trace mineral concentrations. Weight ranges associated with feeding phases also were collected. In total, 18 production systems representing approximately 2.3 million sows (~40% of the U.S. sow herd) participated in the survey. Data were compiled into relatively consistent weight ranges across all participating producers. There were three nursery phases (Phase 1, weaning to 15 lb; Phase 2, 15 to 25 lb; and Phase 3, 25 to 50 lb), four finishing phases (early, 50 to 120 lb; mid, 120 to 220 lb; late, 220 lb to Market; and late with ractopamine HCl, 220 lb to Market), and four breeding herd diets (gilt development, gestation, lactation, and boar). Results were compiled and pooled to determine descriptive statistics on the supplementation rates. Descriptive statistics used included: average, weighted average (determined by size of operation), standard deviation, median, minimum, maximum, 25thpercentile (lowest quartile), and 75thpercentile (highest quartile). Within each dietary phase, the nutrients of interest were: vitamins A, D, E, and K; thiamin; riboflavin; niacin; pantothenic acid; pyridoxine; biotin; folic acid; vitamin B12; choline; betaine; vitamin C; carnitine; Cu; I; Fe; Mn; Se; Zn; Co; and Cr. Average supplementation rates for vitamins and trace minerals within each phase of production were compared to the requirement estimates reported in the NRC (2012). Results indicated tremendous variation in supplementation rates, but most vitamins and trace minerals were included at levels above the requirement estimates reported in the NRC (2012). Along with vitamin and trace mineral supplementation rates, respondents were asked about sources of specific nutrients used in premixes. The most distinguishable differences among sources within this survey were associated with the vitamin D3from a cross-linked vitamin A/D3beadlet, use of natural (d-α-tocopherol) vitamin E, and the use of organic trace minerals (Cu, Mn, Se, and Zn). Ultimately, evaluating current supplementation practices can be used to develop future experimental designs to test vitamin and trace mineral supplementation practices.
Keywords: survey; swine industry; trace minerals; vitamins